Some keys to Jewish humour in the “Humour Prose” by Alejandra Pizarnik - Daza D., Paulina (2016)
Alejandra Pizarnik's "Humour Prose", compiled in her Complete Prose (2008), is an important demonstration of the work developed by the writer during her latest years, her intense language work and its relation to writing; her vital activity as well as the artistic and literary work of her oeuvre. This article aims to promote a rapprochement between the humoristic pizarnikian prose and some features of Jewish humour that seem to establish on her work as evidence of a cultural link that started with a primary and secondary double education, and continued showing on her letters, journals and private conversations registered by her closest circle. It is suggested that the result of the artistic and cultural link gives rise to a laughter that benefits her and helps her to carry the weight of imminent death and madness.